Evaluation of Climatic Comfort of Living Environment based on Age Differentials in Beijing-Tianjin-Hebei Area - Siyu Liu; Buju Long; Zhihua Pan; Fei Lun; Yu Song; Weiying Yuan; Na Huang; Ziyuan Zhang; Shangqian Ma (Ecosystem Health and Sustainability, 2020)
Somatosensory comfort is mainly determined by the Temperature and Humidity Index (THI) with Wind Efficiency Index (WEI), but this conventional usage of these indicators does not capture the age-related differentials. Here we resolved this gap with a modification of the climatic comfort definition and method in a national standard, denoted as the Relative Climate Sensitive Index (RCSI), which incorporated the age-related vulnerability scores determined through online questionnaires with a scoring method, for each of the age-related and adaptive climatic comfort responses to changes in residence with Beijing-Tianjin-Hebei (BTH) region as an example. First, the result showed that the human comfort of living environment decreased with age in the BTH region, implicating age obviously impacted comfort, and weak adaptability made the elderly the relatively most high-risk group – their suitable region was less than a quarter of the whole study region. Second the adverse effects of persistent hot weather on comfort, indicating global warming as the leading driver of dwindling comfort over recent years. As the warming was more significant in the southeastern part, all these forces combined had there a hotspot, appealing for extra attention. Last this improved evaluation accorded with actual situation to captured high-risk groups with their distributions.